2009
DOI: 10.1095/biolreprod.108.075648
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of Beta-Catenin in Uterine Stroma and Smooth Muscle Leads to the Development of Mesenchymal Tumors in Mice1

Abstract: Leiomyomas and other mesenchymally derived tumors are the most common neoplasms of the female reproductive tract. Presently, very little is known about the etiology and progression of these tumors, which are the primary indication for hysterectomies. Dysregulated WNT signaling through beta-catenin is a well-established mechanism for tumorigenesis. We have developed a mouse model that expresses constitutively activated beta-catenin in uterine mesenchyme driven by the expression of Cre recombinase knocked into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
132
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(140 citation statements)
references
References 46 publications
5
132
0
3
Order By: Relevance
“…Focal retention of the MD could occur if expression and accumulation of CA β-catenin is delayed until after E13.5 because removing MIS-producing testes from the organ culture assay after only 1 d of incubation still results in MD regression (33). Delayed expression of Amhr2-Cre could also explain the discrepancy between the previously reported requirement for nuclear β-catenin during MD regression (15) and normal differentiation of reproductive tract tissues in female mice with CA β-catenin expression in the MD mesenchyme (17). This leads us to speculate whether induced expression of CA β-catenin earlier than that which we achieved by Cre expression in the Amhr2 locus might result in greater MD retention.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Focal retention of the MD could occur if expression and accumulation of CA β-catenin is delayed until after E13.5 because removing MIS-producing testes from the organ culture assay after only 1 d of incubation still results in MD regression (33). Delayed expression of Amhr2-Cre could also explain the discrepancy between the previously reported requirement for nuclear β-catenin during MD regression (15) and normal differentiation of reproductive tract tissues in female mice with CA β-catenin expression in the MD mesenchyme (17). This leads us to speculate whether induced expression of CA β-catenin earlier than that which we achieved by Cre expression in the Amhr2 locus might result in greater MD retention.…”
Section: Discussionmentioning
confidence: 93%
“…We have previously reported that expression of CA β-catenin restricted to the uterine stroma and myometrium leads to myometrial smooth muscle cell hyperplasia and development of mesenchymal tumors in murine uteri (17). We and others have also shown that CA β-catenin causes sterility in males by inhibiting postnatal Sertoli maturation and spermatogenesis (18)(19)(20).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…We have targeted NR2F2 and CTNNB1 in this study based on their significant potential for a causal role in uterine fibroid pathophysiology , Tanwar et al 2009). We report that NR2F2 and CTNNB1 levels are altered in human uterine fibroids and that both proteins display strong blood vessel localisation in myometrial and fibroid tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In uterine biology, CTNNB1 plays roles in menstruation (Nei et al 1999) and implantation (Mohamed et al 2005, Jeong et al 2009) and has been linked to endometrial hyperplasia and cancer (Fukuchi et al 1998, Nei et al 1999, Jeong & McMahon 2005. Suggestive of a causative role in uterine fibroid development is the observation that sustained Ctnnb1 expression in transgenic mice results in uterine mesenchymal tumours, which are histologically similar to human uterine leiomyoma (Tanwar et al 2009). NR2F2 belongs to the steroid/thyroid hormone receptor superfamily and plays important roles in development, including cell differentiation, cell cycle and migration, and angiogenesis (see review Boudot et al (2011)).…”
Section: Introductionmentioning
confidence: 99%